2022
DOI: 10.3390/educsci12030190
|View full text |Cite
|
Sign up to set email alerts
|

Deal Me in: Playing Cards in the Home to Learn Math

Abstract: Recent meta-analyses have demonstrated a significant association between children’s early math achievement and their experiences with math at home, including their caregivers’ talk about math. However, few studies have investigated the relations between caregiver math talk and children’s learning with experimental designs. Eighty-six children (M = 5.0 years) and their caregivers were randomly assigned to play either a numeracy or a shape card game at home for six weeks. Data were collected on children’s number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Our cross-sectional results from Study 1 hint that this might be the case, but explicit experimental testing is required. One previous training study using number card games in the home environment did not find effects of training on children’s number skills (Scalise et al, 2022), but it is unclear the extent to which effects may be moderated by children’s underlying skills. Indeed, our Study 2 results suggest that intervention effects that fail to reach significance may in part be due to variability in who benefits, and a deeper exploration of the skills required may prove fruitful.…”
Section: Discussionmentioning
confidence: 97%
“…Our cross-sectional results from Study 1 hint that this might be the case, but explicit experimental testing is required. One previous training study using number card games in the home environment did not find effects of training on children’s number skills (Scalise et al, 2022), but it is unclear the extent to which effects may be moderated by children’s underlying skills. Indeed, our Study 2 results suggest that intervention effects that fail to reach significance may in part be due to variability in who benefits, and a deeper exploration of the skills required may prove fruitful.…”
Section: Discussionmentioning
confidence: 97%
“…The findings of short‐term effects echo those of some successful home training studies that have relied upon parent–child interaction, though they are contrary to others. Using a parent–child card game, Scalise et al (2022) found no effects of randomization to a number game condition as compared to a shape game condition. However, there may be something critical to the inherent embeddedness of a number line in board games or to connecting number words with physical actions (de Vries et al, 2021; Siegler & Ramani, 2009; Whyte & Bull, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Effective number game interventions have nearly exclusively taken place in classroom settings and been administered by a trained game partner (i.e., a researcher or paraprofessional; Ramani et al, 2012) with some noted exceptions (cf., Scalise et al, 2022;Sonnenschein et al, 2016). More recent evidence has suggested that games played with parents at home might be less efficacious than those played with a trained partner (Ramani & Scalise, 2020).…”
Section: Math In the Home Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, playing two different versions of a commercially available number board game or a color board game did not yield any differences in children's improvements in counting and numeral identification post-intervention (Sonnenschein et al, 2016). Similarly, two studies showed that playing a card game that required number comparisons did not yield any significant improvements in children's numerical knowledge compared to a card game that required shape or color matching (Ramani & Scalise, 2020;Scalise et al, 2022).…”
Section: Board and Card Gamesmentioning
confidence: 99%